2016
DOI: 10.4143/crt.2015.296
|View full text |Cite
|
Sign up to set email alerts
|

Splenomegaly and Its Associations with Genetic Polymorphisms and Treatment Outcome in Colorectal Cancer Patients Treated with Adjuvant FOLFOX

Abstract: PurposeSplenomegaly is a clinical surrogate of oxaliplatin-induced sinusoidal obstruction syndrome (SOS). We investigated development of splenomegaly and its association with treatment outcome and genetic polymorphisms following adjuvant 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX) in colorectal cancer (CRC) patients.Materials and MethodsSplenomegaly was determined by spleen volumetry using computed tomography images obtained before initiation of chemotherapy and after completion of adjuvant FOLFOX in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Splenomegaly was determined higher in patients who did not receive dose reduction during chemotherapy in our study, which can be explained by the increase in cumulative oxaliplatin dosage received by patients whose dosages were not reduced. Kim et al have shown that splenomegaly developed more in patients receiving full-dose oxaliplatin than those receiving dose reductions, which is similar to our study [10].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Splenomegaly was determined higher in patients who did not receive dose reduction during chemotherapy in our study, which can be explained by the increase in cumulative oxaliplatin dosage received by patients whose dosages were not reduced. Kim et al have shown that splenomegaly developed more in patients receiving full-dose oxaliplatin than those receiving dose reductions, which is similar to our study [10].…”
Section: Discussionsupporting
confidence: 92%
“…Kim et al have investigated the association between splenomegaly development in patients with colorectal cancer and thrombocytopenia receiving adjuvant FOLFOX therapy similar to ours. The authors have reported that thrombocyte count was lower both during the chemotherapy period and after in patients developing splenomegaly [10]. Moreover, it has also been shown that thrombocytopenia developing in splenomegaly patients was more severe than in those who did not develop splenomegaly [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations